Red Ed: Teaching Toward a New Internationalism - Stephen Paur (Radical Teacher, 2023)
In this essay, I narrate part of my experience leading second-language college writing students through an activity that introduces them to some of the basics of ideology critique and critical discourse analysis. I also describe a Language Event Analysis assignment that invites students to analyze international language-related current events. In the process, I try to show why a dialectical multilingualism must be part of any radically internationalist socialist teaching praxis.